Co-composting of organic solid waste and sewage sludge – a waste management option for University Campus - Fei-Baffoe, Bernard; Osei, Kenneth; Agyapong, Eric Appiah; Nyankson, Eugene Atta (International Journal of Environment, 2016)
Co-composting organic solid waste with dewatered sewage sludge was carried out to determine its suitability for managing waste on a University campus. Windrow composting method was employed in which dewatered sewage sludge and organic solid waste were mixed at volume ratios: 1:1, 1:2, 1:3, 0:1 and 1:0 sludge/organic solid waste. Parameters such as pH, percentage N, C, P, K, Ca, Mg, organic matter, ash content and C/N ratio were determined weekly. Total and faecal coliform population were measured biweekly with Pb and Cd levels determined at the beginning and end of the composting. With the exception of ratio 1:0 sludge/organic solid waste, all other ratios attained a favourable Carbon to Nitrogen (C/N) ratio both at the start and end of the composting process. Levels of major nutrients measured were found to be favourable for use as organic fertilizer. There was a general decline in carbon and organic matter in all the compost piles except the sewage sludge pile (1:0). Apart from the compost ratio 1:0 sludge/organic solid waste, all other ratios attained a temperature of 55°C within 8 days of composting. Generally the compost ratios 1:2, 1:3 and 0:1 (sludge/organic solid waste) were found to be the most suitable for use as organic fertilizer. International Journal of Environment Vol. 5 (1) 2016, pp: 14-31